Age estimation for disorder characterization from pediatric polysomnograms - Festag, Sven; Herberger, Sebastian; Spreckelsen, Cord; Krefting, Dagmar; Fietze, Ingo; Penzel, Thomas; Marschik, Peter B.; Spicher, Nicolai (Biomedical signal processing and control, 2025)
Estimating biological age via deep neural networks (DNNs) processing polysomnograms (PSGs) showed promising results in adults. While age estimation it…
Online veröffentlicht am 20. Februar 2025
Gesehen am 18.11.2025